2004
DOI: 10.1046/j.1474-919x.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Seychelles Warblers fail to recolonize nearby islands: unwilling or unable to fly there?

Abstract: The Seychelles Warbler Acrocephalus sechellensis is a rare island endemic which, from 1920 to 1988, occurred only on Cousin Island (29 ha) in the Seychelles. Despite the saturated nature of this population and the possibility of obtaining higher reproductive success on new nearby islands, inter‐island dispersal by Seychelles Warblers is extremely rare (0.10%). We test the hypothesis that Seychelles Warblers show an adaptation typical for island birds: a low‐cost reduced‐size flight apparatus. We compared the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 25 publications
0
134
1
Order By: Relevance
“…This is also the case for the Seychelles warbler. Despite the over-production of warblers on Cousin in the last decades, only two warblers (0.13%, N = 1599 banded birds) have crossed the small stretch of sea (1.6 km) between Cousin and Cousine unaided (Komdeur et al, 2004).…”
Section: Numerical and Genetic Resilience Of Island Populations Towarmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also the case for the Seychelles warbler. Despite the over-production of warblers on Cousin in the last decades, only two warblers (0.13%, N = 1599 banded birds) have crossed the small stretch of sea (1.6 km) between Cousin and Cousine unaided (Komdeur et al, 2004).…”
Section: Numerical and Genetic Resilience Of Island Populations Towarmentioning
confidence: 99%
“…If a colour-ringed bird was missing from its territory, the rest of the island was searched for it. Off-island migration by warblers is negligible (0.13% per annum; Komdeur et al, 2004), so birds that have disappeared were considered to be dead. Breeding activity was assessed by following each female continuously for 30 min and recording whether she was nestbuilding, incubating, or feeding young.…”
Section: Breeding Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Seychelles Warbler (Acrocephalus sechellensis) shows locomotory structures similar to those found in closely related species that can sustain flight over long distances, but does not manage to disperse successfully to islands with suitable habitats just outside its distribution range (Komdeur et al, 2004). Thus, to investigate the causes of population divergence at a small spatial scale, it is important to be able to tease apart the effects of gene flow from those due to selection and drift at the relevant spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…During the breeding seasons, all territories were checked for the presence of warblers at least once every two weeks. As inter-island dispersal is extremely rare (0.1%, N = 1924, Komdeur et al, 2004) warblers that were missing from their territory and not found on other territories can safely be assumed dead. Dispersal data was based on individuals that were colour-ringed on their natal territory from 1985 to 2005.…”
Section: Study Populationmentioning
confidence: 99%